Kisruh Alih Fungsi Rumah Ibadat: Kasus Gereja Kristen Injili Nusantara Kawanan Domba Salatiga - Marmiati Mawardi (Balai Penelitian dan Pengembangan Agama Semarang, 2016)
The use of a dwelling house as a place for public worship/church has been created conflict among believers. This is happened in a village called Ngawen, Mangunsari, Salatiga. This study aims to explore the triggering factors of conflict between the Muslim community and the board of Gereja Kristen Injili Nusantara (GKIN) “Kawanan Domba”. This research uses a qualitative approach. Data were gathered using a Focus Group Discussion approach. Findings of this study show that such house was built based on the IMB of dwelling place; the board of church has no temporary authorization to use that house as a place of worship. The community objects and indisposed for the existence of a church due to various reasons. This almost leads to a physical conflict. The government officers mediate two conflicting parties to meet and resolve the problem. This meeting made an agreement between them that the activities of the church were stopped. But in reality, the church still conducted some activities